International Law Enforcement Against Transnational Narcotics Smuggling In Indonesian Sea Lanes - Nashira Ryan, Az Zahra; Prastyanti, Rina Arum (International Journal of Social Research, 2024)
Indonesia, as the world’s largest archipelagic country, occupies a strategic position in the Asia-Pacific region, which makes its sea lanes vulnerable to transnational narcotics smuggling. Narcotics trafficking through Indonesian waters not only disrupts national security but also has far-reaching consequences for international security, global politics, and human rights. Despite existing international legal frameworks such as the 1982 United Nations Convention on the Law of the Sea (UNCLOS) and the 1961 Single Convention on Narcotic Drugs, Indonesia faces significant enforcement challenges. These include vast maritime borders, limited resources for surveillance, and the involvement of sophisticated international criminal syndicates. This research aims to analyze international law enforcement efforts in combating narcotics smuggling in Indonesian sea lanes, focusing on both legal frameworks and the practical challenges faced in enforcement. The study uses a normative legal research method, examining secondary data from legal documents, books, and journals. The results indicate that while international cooperation frameworks have been established, the effectiveness of narcotics law enforcement remains hindered by logistical and technological gaps. The study concludes that improving international collaboration, enhancing surveillance technology, and strengthening community-based preventive measures are essential for combating narcotics trafficking in Indonesian waters effectively.